PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT DAN LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI INDEKS SAHAM SYARIAH INDONESIA (ISSI) PERIODE 2019-2023 - M Randi Saputra; Winda Rosalia; Elyanti Rosmanidar; Mohammad Orinaldi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The aim of this research is to determine the effect of disclosure of sustainability reports and leverage on the financial performance of manufacturing companies listed on the Indonesian sharia stock index (ISSI) for the 2019-2023 period. This research uses secondary data in the form of reports on the company's financial condition which are made periodically. Obtained via the official website of the Indonesian Stock Exchange. Samples were taken using a purposive sampling technique, totaling 9 companies. This research uses quantitative methods with data analysis methods, namely using panel data regression which is processed using the E-Views 12 application. The research results show that only partially, economic performance has an effect on the financial performance of manufacturing companies. Meanwhile, it simultaneously has an influence on the financial performance of manufacturing companies